2011
DOI: 10.1117/12.881919
|View full text |Cite
|
Sign up to set email alerts
|

DEA material enhancement with dipole grafted PDMS networks

Abstract: Silicone elastomers are highly suitable for application in the field of dielectric elastomer actuators (DEA) due to their unique material properties (e.g. low glass temperature, thermal stability, large capability of chemical tailoring). The elastomer forming Polydimethysiloxane (PDMS) employed for this study consists of chains with vinyl termination and is cross linked via hydrosilylation to a cross linking molecule in the presence of platinum catalyst. Here, dipole molecules (N-Allyl-N-methyl-4-nitroaniline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…For reference samples, these values are higher as compared with those reported in literature for room temperature vulcanization silicones [35,36]. Most of the values for our composites are comparable with those reported for polydimethylsiloxanes filled with encapsulated conductive polyaniline particles [7] or with commercial silicone Elastosil grafted with polar group but lower as compared with those obtained for Sylgard grafted with the same polar groups [37].…”
Section: Figuresupporting
confidence: 81%
See 1 more Smart Citation
“…For reference samples, these values are higher as compared with those reported in literature for room temperature vulcanization silicones [35,36]. Most of the values for our composites are comparable with those reported for polydimethylsiloxanes filled with encapsulated conductive polyaniline particles [7] or with commercial silicone Elastosil grafted with polar group but lower as compared with those obtained for Sylgard grafted with the same polar groups [37].…”
Section: Figuresupporting
confidence: 81%
“…The polarizability of the Si-O bond that constitutes a premise for a high dielectric constant is higher as compared to organic nonpolar polymers (e.g., polyethylene), but in reality, this is not so much due to the side methyl groups (in the case of PDMS), which prevent Si-O dipoles from approaching each other too closely) [6]. In order to increase the dielectric constant, the polysiloxanes are chemically modified by attaching polar groups, such as N-Allyl-N-methyl-4nitroaniline [7], cyanalkyl [8], etc. to the silicon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…-The use of an elastomeric membrane with a higher relative permittivity to increase the device's capacitance. Several research groups have attempted to disperse nano particles (titanium dioxide, BaTiO 3 ) or dipole molecules into silicones in order to increase the permittivity of the elastomer [97][98][99]. However, the increase of the permittivity often comes at the cost of a reduced dielectric breakdown field.…”
Section: Towards Low Actuation Voltagesmentioning
confidence: 99%
“…Previous studies on the enhancement of ε r have shown destruction of elasticity upon high loadings of filler particles either due to crystallinity effects 3,4 or solvent effects 5 .…”
Section: Introductionmentioning
confidence: 99%